Clinical characteristics and comorbidities of elderly asthmatics who attend allergy clinics - Anahí Yáñez; Marcela Soria; Susana De Barayazarra; Nancy Recuero; Francisco Rovira; Edgardo Jares; Ana María Stok; Sergio Nemirovsky; Carlos Bueno (Asthma Research and Practice, 2018)
Abstract Background To date, few studies have focused on the clinical and allergic characteristics of asthma in the elderly, defined as asthma in people aged 60 or over. Thus, we propose to identify and study the clinical and allergic characteristics and comorbidities of patients with asthma among the elderly. Methods A retrospective, observational, descriptive study was developed in five clinics and hospitals in Argentina. Allergy Physicians analyzed their patients’ medical records in 2014 and included those adults over the age of 60, who had been diagnosed with asthma according to the GINA guidelines. Clinical and allergic characteristics were analyzed. Results A total of 152 patients diagnosed with asthma, of whom 73% were women and 11% ex-smokers, were included in this study, with a mean age of 66 years. Only 10.5% of the participants had onset asthma past the age of 60. Regarding asthma severity, 74.3% were diagnosed with moderate persistent asthma, and 7.2% with severe persistent asthma. Eighty-four percent of the patients were treated with an inhaled corticosteroid (ICS) along with a long-acting β 2-adrenergic agent (LABA). More than half of the patients had two or more comorbidities simultaneously. Allergic comorbidities were the most frequent comorbidities, followed by arterial hypertension. Among allergic comorbidities, most patients presented allergies at the nasal level. There were no significant differences between the subpopulations of patients with late-onset asthma (LOA) and asthma with onset before the age of 60, i.e. early onset asthma (EOA) in most of their clinical characteristics. However, it was observed that EOA accounted for a higher percentage of patients with nasal allergies as compared to LOA (71% vs 46%, p <  0.05).It is worth mentioning that almost half of the patients with LOA had allergies at the nasal level. Conclusion These results may provide a better understanding of the clinical characteristics of asthma in the elderly in Argentina, thus, enabling the development of future therapeutic strategies and a better quality of life for our elderly asthma patients.